Analysis of Flying Fox Sports Tourism Development in Sangiang Bedil Sumedang Using the MSP DM Approach - M Rifky Ilyansah Tantri; Rizal Ahmad Fauzi; Adang Sudrajat (Journal Coaching Education Sports, 2026)
This study aims to analyze the potential development of flying fox sport tourism in Sangiang Bedil, Darmaraja District, Sumedang Regency, using the Marketability, Sustainability, Participatory, and Disaster Mitigation (MSP+DM) approach. A descriptive qualitative method was employed through observation, interviews, and documentation involving tourism managers, flying fox operators, and visitors as research informants. Data were analyzed using thematic coding techniques supported by data triangulation to ensure validity and reliability. The findings indicate that the marketability aspect is strengthened by digital promotion through social media platforms such as TikTok, Instagram, and YouTube, supported by natural hill landscapes and adventure-based tourism experiences. In terms of sustainability, the attraction contributes positively to the local economy by creating employment opportunities and supporting small businesses, although environmental pressure and economic dependency on tourism remain challenges. Community participation is reflected in operational involvement, environmental maintenance, and tourism-supporting businesses; however, participation in strategic decision-making is still limited. Regarding disaster mitigation, safety measures such as routine equipment inspections, safety briefings, temporary operational closure during bad weather, and first-aid facilities have been implemented, although more structured standard operating procedures and emergency response training are still required. Overall, flying fox tourism in Sangiang Bedil has strong potential to become a competitive nature-based sport tourism destination through improved promotion, community involvement, environmental management, and risk mitigation systems.